Cross-cultural adaptation, reliability and validity of the Turkish version of the Lower Limb Functional Index. (18th December 2015) - Duruturk, Neslihan; Tonga, Eda; Gabel, Charles Philip; Acar, Manolya; Tekindal, Agah
Abstract: Purpose : This study aims to adapt culturally a Turkish version of the Lower Limb Functional Index (LLFI) and to determine its validity, reliability, internal consistency, measurement sensitivity and factor structure in lower limb problems. Method : The LLFI was translated into Turkish and cross-culturally adapted with a double forward–backward protocol that determined face and content validity. Individuals ( n = 120) with lower limb musculoskeletal disorders completed the LLFI and Short Form-36 questionnaires and the Timed Up and Go physical test. The psychometric properties were evaluated for the all participants from patient-reported outcome measures made at baseline and repeated at day 3 to determine criterion between scores (Pearson's r ), internal consistency (Cronbachs α ) and test–retest reliability (intraclass correlation coefficient – ICC2.1 ). Error was determined using standard error of the measurement (SEM) and minimal detectable change at the 90% level (MDC90 ), while factor structure was determined using exploratory factor analysis with maximum likelihood extraction and Varimax rotation. Results : The psychometric characteristics showed strong criterion validity ( r = 0.74–0.76), high internal consistency ( α = 0.82) and high test–retest reability (ICC2.1 = 0.97). The SEM of 3.2% gave an MDC90 = 5.8%. The factor structure was uni-dimensional. Conclusions : Turkish version of LLFI was found to be valid and reliable for the measurement of lower limb function in a Turkish population. Implications for Rehabilitation: Lower extremity musculoskeletal disorders are common and greatly impact activities among the affected individuals pertaining to daily living, work, leisure and quality of life. Patient-reported outcome (PRO) measures have advantages as they are practical, cost-effective and clinically convenient for use in patient-centered care. The Lower Limb Functional Index is a recently validated PRO measure shown to have strong clinimetric properties.